Bioinformatics -- a student's companion - Ibrahim, Kalibulla Syed; Gurusubramanian, Guruswami; Zothansanga; Yadav, Ravi Prakash; Kumar, Nachimuthu Senthil; Pandian, Shunmugiah Karutha; Borah, Probodh; Mohan, Surender (Springer, 2017)
This manual offers a stand-alone reading companion, unique in simplifying the practical components of Bioinformatics in a unique and user-friendly manner. It covers the practical component of syllabi used at most leading universities and discusses the most extensively used tools and methodologies in Bioinformatics. Research in the biological sciences has made tremendous strides in recent years due in part to the increased automation in data generation. At the same time, storing, managing and interpreting huge volumes of data has become one of the most challenging tasks for scientists. These two aspects have ultimately necessitated the application of computers, giving rise to a highly interdisciplinary discipline?Bioinformatics. Despite the richness of bioinformatics resources and methods, the exposure of life sciences undergraduates and postgraduates to bioinformatics is extremely limited. Though the internet offers various tools for free, and provides guides for using them, it fails to help users interpret the processed data. Moreover, most sites fail to update their help pages to accommodate software upgrades. Though the market is flooded with books discussing the theoretical concepts in Bioinformatics, a manual of this kind is rarely found. The content developed to meet the needs of readers from diverse background and to incorporate the syllabi of undergraduate and postgraduate courses at various universities.
Keywords: Bioinformatics.; elektronické knihy; electronic books